Exploring the role of brand trust in the relationship between brand associations and brand loyalty in sport and fitness. (14th January 2008) - Filo, Kevin; Funk, Daniel C.; Alexandris, Kostas
Brand loyalty has emerged as a complex construct with a wide variety of antecedents that have been evaluated in the existing research. Using the psychological continuum model (PCM) as its theoretical framework, this paper examines the mediational role of brand trust in the relationship between brand associations and loyalty within two separate contexts of the sport brand environment. In making this examination, the authors try to determine whether brand trust does impact this relationship as well as whether this impact is different between the two separate contexts. A questionnaire was distributed to two separate samples (N=70 and 100) to measure seven brand associations, brand trust and brand loyalty and compare results for managed sport brands versus a fitness brand. Results reveal that brand trust mediates the link between brand loyalty and the management and popularity of the brand across both samples. For the managed sport brands, the links between brand loyalty and both nostalgia and vicarious achievement were also mediated. The authors propose that brand managers work to leverage brand trust through social responsibility, consumer satisfaction and quality customer service in an effort to increase consumer brand loyalty.